2021
DOI: 10.3390/life11020117
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity in Depression or Depression in Adiposity? The Role of Immune-Inflammatory-Microbial Overlap

Abstract: Some of the most common and debilitating conditions are metabolic disorders (metabolic syndrome and non-alcoholic fatty liver disease) and depression. These conditions are also exacerbated by the fact that they often co-occur. Although the exact mechanisms underlying such relationships are poorly known, antipsychotic medication and antidepressant use, diet and physical activity, and lifestyle factors are believed to play a role; however, their high co-occurrence rate suggests a possible pathophysiological over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…The Global Burden of Disease study from 1990 to 2017 reported a 49.86% increase in the incidence of depression (5), with at least one in five people experiencing depression in their lifetime (6)(7)(8). Depression is often comorbid of many chronic diseases and incrementally worsens health outcomes (9,10). Multiple community-and population-based studies have reported that patients with depression have a 2-fold increased risk of developing metabolic syndrome (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The Global Burden of Disease study from 1990 to 2017 reported a 49.86% increase in the incidence of depression (5), with at least one in five people experiencing depression in their lifetime (6)(7)(8). Depression is often comorbid of many chronic diseases and incrementally worsens health outcomes (9,10). Multiple community-and population-based studies have reported that patients with depression have a 2-fold increased risk of developing metabolic syndrome (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Some suggest HPA‐axis overactivity to be related to melancholic depression and underactivity to non‐melancholic depression. 14 These differences attempt to explain parts of the pathophysiology of depression and its subtypes, 13 but much still remains unknown.…”
Section: Mortality and Depressive Symptoms‐findings From Helsinki Bir...mentioning
confidence: 99%
“…Reduced gut microbial diversity is now known to be associated with a variety of diseases such as: depression, autism, obesity, hypercholesterolemia, diabetes, inflammatory bowel disease, allergies, polycystic ovary syndrome, nonalcoholic fatty liver disease, colon cancer, and liver cancer [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In animal experiments, it is suggested that some microbial community alterations can directly lead to disease states [ 10 ].…”
Section: Introductionmentioning
confidence: 99%